SPECIFIC CHARACTERISTICS OF THE SPIRTUAL AND ETHICAL VIEWS OF MAHMUDKHOJA BEHBUDI (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article talks about the specific characteristics of the spiritual and moral ideas of Mahmudkhoja Behbudi, a bright manifestation of the Turkestan modernist movement, playwright, enlightened populist, and their importance in the education of the young generation. Aspects of Behbudi's pedagogical views and scientific activities that can serve as an example for the education of today's young generation are analyzed.